The Relationship Between Self-Compassion And The Mental State Of Football Athletes - Dika, Andika Prasetia Ramadhan; Adang sudrazat; Entan Saptani (UNIB Press, 2025)
This study aims to determine the relationship between self-compassion or self-compassion and the mental condition of soccer athletes. Self-compassion is a positive attitude that involves acceptance and gentleness towards oneself when experiencing failure or pressure. In the world of sports, especially soccer, a stable and positive mental condition is very important for players to be able to perform optimally and face pressure on the field. The results of the study showed that there was a significant positive relationship between the level of self-compassion and good mental condition in soccer athletes. Athletes who are able to be gentle and understanding towards themselves usually show calmness, self-confidence, and better ability to control emotions. Developing a self-compassion attitude can help athletes to recover after experiencing failure and stay motivated in achieving their best performance. Based on these findings, it is recommended that coaches and related parties pay attention to the mental health aspects of players through self-compassion training and coaching. By increasing sensitivity to mental conditions, it is hoped that players will not only excel technically and physically, but also have mental strength that can support their success on the field and in everyday life. Self-compassion is one of the important keys in building a strong and happy warrior mentality in sports.